Outcomes of drain versus no drain in total knee arthroplasty: a retrospective cohort study - Anas Albasha (17765964) (2023)
Purpose The use of suction drains in total knee arthroplasty (TKA) remains controversial. The aim of this study is to compare the outcomes of patients who received suction drains versus those who did not, focusing on blood loss, blood transfusion need, and length of hospital stay. Methods A retrospective observational cohort study was conducted at a tertiary hospital between January 1, 2015, and December 30, 2019, and included 262 patients who underwent unilateral non-traumatic primary TKA and were over 18 years old. The Institutional Review Board (IRB) approved the study (MRC-02–20-278). Results A total of 262 patients were included, with an age range of 47 to 91 years. Most of the included patients were females, 74.4% (195). Hypertension was the most frequent risk factor, 67.6%, followed by diabetes. Of 262 patients, 156 (59.5%) received a drain. The drain group had significantly longer hospital stay, 30% longer tourniquet time, greater haemoglobin and haematocrit drops, higher count of transfused packed RBC units, and lower use of anticoagulants. Moreover, tranexamic acid (TXA) use (n = 106) in surgery reduced hospital stays, tourniquet time, drain output, and increased pre- and postoperative haemoglobin and hematocrit levels compared to no TXA group (n = 156) (p < 0.05, z-score reported). Conclusions This study found that patients who received a drain had longer hospital stays and greater blood loss and transfusion rates compared to those who did not. The use of TXA in surgery was associated with improved outcomes and reduced overall complications. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-023-05946-z